(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
The pilot trial on AquatabsTM disinfectant tablets was undertaken over a period of one month (three 10-day period excluding the pre- and post-trial activities) during October-December 2004 in an area of low-income urban communities suffering from a lack of basic health services including a lack of adequate and safe water and sanitation facilities (Lalbagh) as well as adjacent areas of old Dhaka. Drinking water consumed by 347 persons was treated in 50 households comprising 70 children under 5 years old. A pre-trial survey and testing of the water supplies demonstrated that the mean faecal coliform count was > 103 MPN/100mL and that all children (100%) belonged to a "Severe Diarrhoea Group" (> 3 incidences of light diarrhoea or any serious diarrhoeal condition). One effervescent AquatabsTM (67mg sodium dichloroisocyanurate) was added by the mother to the local container (filled from a community tap or standpipe, often through an illegal connection), which held about 20-25 litres of unsafe water, giving a dosage of about 2mg/L free chlorine. During the trial period water samples were tested at 3 x 10-day period for free residual chlorine levels and faecal coliform counts at all households. About 65.7% of children were reported to be free from diarrhoea during the trial period, there was a strong association between "under-chlorinated" water (<0.5mg/L residual free chlorine) and reported diarrhoea incidences. Survey analysis during the pilot trial concluded that 70% of mothers were not aware that health improvements were related to water supply and sanitation. Keywords: AquatabsTM, Diarrhoea, Low income urban community. DOI: 10.3329/bjsir.v44i2.3679 Bangladesh J. Sci. Ind. Res. 44(2), 233-240, 2009